2013
DOI: 10.1080/10400435.2012.715113
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Older Adults with Dementia in Creative Occupations Using Artificially Intelligent Assistive Technology

Abstract: Engagement in creative occupations has been shown to promote well-being for older adults with dementia. Providing access to such occupations is often difficult, as successful participation requires face-time with a person who is knowledgeable in facilitating engagement as well as access to any required resources, such as an arts studio. In response, a computer-based device, the Engaging Platform for Art Development (ePAD), was created to with the aim of enabling more independent access to art creation, ePAD is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 14 publications
1
55
0
Order By: Relevance
“…Several of the aforementioned articles have featured games or leisure activities; however, these have been designed to assess cognition [21,26], provide cognitive stimulation [37,45], or to assist in the delivery of therapeutic interventions [40,41]. Very few studies focused on games or activities purely for entertainment or leisure purposes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of the aforementioned articles have featured games or leisure activities; however, these have been designed to assess cognition [21,26], provide cognitive stimulation [37,45], or to assist in the delivery of therapeutic interventions [40,41]. Very few studies focused on games or activities purely for entertainment or leisure purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Programs and apps presented on touchscreen devices can be designed to facilitate customization, which allows for easy adaptation and consequently they can be responsive to the needs of the users [13,25,37,40,41]. Presenting customization options within programs in an accessible format allows a caregiver or therapist to tailor the program to each individual [40,41].…”
Section: Resultsmentioning
confidence: 99%
“…Leuty et al 44 Linking trial outcomes to process evaluation findings Only 24 studies (21 interventions) reported the use of a theoretical framework or a research framework to inform the decision-making and design of the process evaluation. As a result, reasoning behind used approaches and methodologies was rarely described.…”
Section: Investigating Participants' Opinionmentioning
confidence: 99%
“…Musical memory is relatively spared in dementia [39] and multiple technology projects have leveraged this including the one-button radio [40], simple music-making interface [41] and collaborative music making [42]. Enjoying art has also led to programmes such as House of Memories 1 , an interactive art installation for care homes [43], making art as an enjoyable pastime [44] and a more focused art therapy programme [45, 46]. …”
Section: Introductionmentioning
confidence: 99%